Youth sport coaches’ role in facilitating positive youth development in Portuguese field hockey - Santos, Fernando de Sousa Ferreira dos (2018)
Researchers have examined youth sport coaches’ role in facilitating positive youth development (PYD). This past research demonstrates that when coaches use an intentional approach to development, they can play an important part in helping young people to reach adulthood with the necessary competencies to face the social challenges ahead. However, studies within the area of PYD through sport have predominantly emanated from Englishspeaking countries and there remains a need to better understand coaches’ views on PYD within different countries’ sport systems. The purpose of this study was to examine Portuguese coaches’ perspectives on their role in facilitating PYD in youth field hockey. The participants were 11 youth field hockey coaches (2 females and 9 males) who coached athletes between 6 and 18 years of age. Findings showed how the coaches believed PYD could be fostered as they discussed several PYD-related concepts (e.g. life skills) they deemed were being developed in field hockey. However, creating enjoyable environments and talking about life skills with players were the only explicit initiatives discussed by the coaches with the intent of fostering PYD. Coach education was perceived by half the sample as an important learning situation to gain competencies to facilitate PYD, while the other half emphasised that coach education courses were lacking in material associated with this topic. Those who saw value in coach education presented a narrow view of PYD as being solely associated with the psychological aspects of coaching. Moving forward, coach education courses should first be designed to have coaches understand the full spectrum of the concept of PYD and be framed as suitable learning environments where coaches can learn how to foster PYD.